Upper Gastrointestinal Langerhans Cell Histiocytosis: A Report of 2 Adult Cases and a Literature Review. (August 2021) - Matsuoka, Yui; Iemura, Yoshiki; Fujimoto, Masakazu; Shibuya, Shinsuke; Yamada, Atsushi; Fujii, Shigehiko; Kusaka, Toshihiro; Shindo, Takero; Minamiguchi, Sachiko; Haga, Hironori
Langerhans cell histiocytosis (LCH) with primary involvement of the upper gastrointestinal (GI) tract is rare. We report 2 adult cases of localized LCH in the upper-GI tract, including the second reported adult case of esophageal LCH and review 11 previously reported cases. Case 1 involved the esophagus of a 61-year-old man; histiocytosis was detected when endoscopy was performed for an examination of epigastric pain. Case 2 involved the stomach of a 56-year-old woman wherein the lesion was detected during a follow-up endoscopy after Helicobacter pylori infection. Both biopsy specimens exhibited diffuse proliferation of mononuclear cells with nuclear convolution and a background of eosinophilic infiltrate. The cells were immunohistochemically positive for CD1a and langerin, and BRAF V600E mutation was detected in Case 2. Follow-up endoscopy for both cases revealed that the lesions disappeared without any treatment. It is important to avoid misdiagnosing LCH of the upper-GI tract as a malignant neoplasm.